Ninth Review of the International Monetary Fund's Data Standards Initiatives. (Policy Papers; Policy Paper ;, 2015)
The International Monetary Fund's Executive Board regularly reviews progress and developments under the Data Standards Initiatives. The last review-Eighth Review-undertaken in February 2012 introduced the Special Data Dissemination Standard (SDDS) Plus. In light of the long experience under the Data Standards Initiatives established in the mid-1990s, this review takes a longer term retrospective on what has been achieved so far, and highlights some of the lessons learned. What is evident is the contrast between the progress of countries with more advanced dissemination practices (SDDS and SDDS Plus), and the slow pace of improvement under the General Data Dissemination System (GDDS).